Sebab Atau Alasan Hakim Tidak Menjatuhkan Hukuman Maksimal Serta Hambatan yang Dihadapi dalam Penanganan Kasus Pembunuhan Berencana di Jalur 40 Kupang Kota - Melani Yosefine Akunut; Rudepel Petrus Leo; Deddy R (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Premeditated murder is the crime of taking the life of another human being, or killing after planning the time or method, with the aim of ensuring the success of the killing or to avoid capture. Premeditated murder in general law is the most serious type of murder, and the perpetrator may be sentenced to death or life imprisonment. The purpose of this study is to analyze the causes or reasons why the judge did not impose the maximum sentence and the obstacles faced in handling cases of premeditated murder in the Kupang City line This research is an empirical legal research, conducted at the Kupang District Court, Data collection techniques use observation techniques, interviews, and literature/document studies. The results of data management were analyzed descriptively qualitatively using the inductive method. Based on the results of research and discussion, it can be seen: (1) The reason or reason the judge did not give the maximum sentence to the perpetrators of murder on Line 40 Kupang City there are two reasons, namely, the Judge considers the aggravating and mitigating circumstances of the perpetrators. (2) The obstacles faced in handling premeditated murder cases are external and internal factors.